2014
DOI: 10.4184/asj.2014.8.3.227
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Correlates of Low Back Pain in Primary Care: What Are the Contributing Factors in a Rapidly Developing Country

Abstract: Study DesignCross-sectional.PurposeThe purpose of the study was to determine the prevalence of low back pain (LBP) in the primary care setting with emphasis on the socio-demographic contributing factors and impact of LBP on lifestyle habits.Overview of LiteratureLBP is one of the most common medical conditions seen in the Primary Health Care Clinic.MethodsA representative sample of 2,600 patients were approached and 1,829 subjects agreed to participate in this study (70.0%). Data on socio-demographic character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
25
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 28 publications
5
25
1
1
Order By: Relevance
“…A moderate association with WPS and mental health diagnoses was observed among a large sample of US college students. 141 WPS was also associated with greater BMI and risk for obesity after adjusting for cigarette smoking, number of chronic diseases, age, gender, income and marital status in a cross-sectional study of 2536 from Syria 142 Further cross-sectional studies reported elevated urine microalbumin, 143 low back pain 144 and increased risk of gastroesophageal reflux disease among exclusive WP smokers 145 Increased attic retractions, which predispose to cholesteatomas and possibly hearing loss, were reported in 80 ears of WP smokers. 146 WPS was associated with other miscellaneous conditions in several case reports including a case of hand eczema after contact with a WP tube, 147 acute eosinophilic pneumonia, 148 two cases of squamous cell carcinoma and lower lip keratoacanthoma 149 and ulcerative colitis flare after discontinuing WPS.…”
Section: Resultsmentioning
confidence: 96%
“…A moderate association with WPS and mental health diagnoses was observed among a large sample of US college students. 141 WPS was also associated with greater BMI and risk for obesity after adjusting for cigarette smoking, number of chronic diseases, age, gender, income and marital status in a cross-sectional study of 2536 from Syria 142 Further cross-sectional studies reported elevated urine microalbumin, 143 low back pain 144 and increased risk of gastroesophageal reflux disease among exclusive WP smokers 145 Increased attic retractions, which predispose to cholesteatomas and possibly hearing loss, were reported in 80 ears of WP smokers. 146 WPS was associated with other miscellaneous conditions in several case reports including a case of hand eczema after contact with a WP tube, 147 acute eosinophilic pneumonia, 148 two cases of squamous cell carcinoma and lower lip keratoacanthoma 149 and ulcerative colitis flare after discontinuing WPS.…”
Section: Resultsmentioning
confidence: 96%
“…6 On an international level, the reported prevalence of LBP cases reach as high as 56.5% in a population of 1829 people in Qatar. 7 Similarly, the review from Hoy et al 8 showed that in Denmark, the recorded prevalence ranged from 6.3 to 19.3%, 18.9% in Canada, 36% in the United Kingdom, and 18.4% in Israel.…”
Section: Introductionmentioning
confidence: 95%
“…911 The Arab Gulf region has witnessed significant economic changes following the discovery of oil, which transformed lifestyle into one that is more sedentary and includes unhealthy dietary habits. Some of the highest rates of obesity have been reported in this part of the world in recent years, 12 thus predisposing its inhabitants to developing a number of diseases including arthritis.…”
Section: Introductionmentioning
confidence: 99%